Isolation of Antithrombin Globulin from Human Blood Plasma - Shinowara, George Y.; Buckley, Dimite J. (Thrombosis and Haemostasis, 1960)
Fraction III + IV obtained by a low temperature — low ionic strength fractionation procedure was found to contain 97 percent of the antithrombin activity of whole plasma. The mean antithrombin activity in this fraction from 88 normal plasma specimens was 172.6 ± S. D. 19.8 units per ml. Further purification experiments resulted in fraction III representing 96 per cent of the antithrombin activity in fraction III + IV. There was no evidence for fibrinogen, prothrombin and antihemophilic globulin contamination in fraction III. Over 90 per cent of the plasma gamma globulins was present in this fraction.The kinetics of the thrombin-antithrombin reaction were investigated. Under the specific conditions employed, the reaction was found to follow a first order course. The heat of activation was determined to be 11,300 calories. A standard antithrombin unit is defined. A quantitative test procedure which is accurate at both high and low concentrations of the circulating anticoagulant is described and its application on fractions, heat defibrinated plasma and serum is discussed.